The Intersections Between Social Determinants of Health, Health Literacy, and Health Disparities - Schillinger, Dean (Studies in health technology and informatics, 2020)
This chapter synthesizes what is known about the relationship between social disadvantage and measures of low health literacy (LHL), and reviews the research examining whether LHL is an explanatory factor connecting social disadvantage, health outcomes, and health disparities. Written from a U.S. perspective, the chapter then offers a novel conceptual framework that presents how the social determinants of health might interact with LHL to result in health disparities. The framework articulates relationships that reflect public health pathways and healthcare pathways, which include their related health literacies. In addition, the chapter highlights as an exemplar one important potential causal mechanism in the healthcare pathway by exploring the communication model in outpatient care, as communication has been very well-studied with respect to both health disparities and HL. The chapter then, provides two examples of HL interventions aligned with the conceptual framework, one of which addresses the health care literacy pathway, and the other addresses the public health literacy pathway. The chapter continues with a number of cautionary statements based on the inherent limitations of current HL research, including problems and concerns specific to the attribution of HL as an explanatory factor for extant socioeconomic and racial/ethnic health disparities. The chapter closes with recommendations regarding future research directions.